2023
DOI: 10.1038/s41421-023-00535-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive structural analysis reveals broad-spectrum neutralizing antibodies against SARS-CoV-2 Omicron variants

Abstract: The pandemic of COVID-19 caused by SARS-CoV-2 continues to spread around the world. Mutant strains of SARS-CoV-2 are constantly emerging. At present, Omicron variants have become mainstream. In this work, we carried out a systematic and comprehensive analysis of the reported spike protein antibodies, counting the epitopes and genotypes of these antibodies. We further comprehensively analyzed the impact of Omicron mutations on antibody epitopes and classified these antibodies according to their binding patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…While the V H domain had six SHMs, only two of eighteen total residues comprising the heavy chain paratope involved SHMs, whereas all V L domain paratope residues were germline encoded, suggesting that similar to other nAbs isolated following infection ( 23 ), C1596 has minimal somatic mutations involved at the contacting interface. Finally, we compared the binding pose of C1596 to C1791 ( IGHV3-23*01/IGKV1-17*01 ), an antibody described by our group ( 20 ), and S2L20 ( IGHV3-30/IGKV1-33 ) ( 39 ), a previously-described cross-reactive, but weakly neutralizing (IC 50 > 1 ug ml -1 ) antibody ( 80 ) (Supplemental Figure 5C-E). While the NTD footprint was similar across all antibodies and each interacted with the SD1 domain, available structures showed that only C1596 engaged the RBD within the same protomer (Supplemental Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
“…While the V H domain had six SHMs, only two of eighteen total residues comprising the heavy chain paratope involved SHMs, whereas all V L domain paratope residues were germline encoded, suggesting that similar to other nAbs isolated following infection ( 23 ), C1596 has minimal somatic mutations involved at the contacting interface. Finally, we compared the binding pose of C1596 to C1791 ( IGHV3-23*01/IGKV1-17*01 ), an antibody described by our group ( 20 ), and S2L20 ( IGHV3-30/IGKV1-33 ) ( 39 ), a previously-described cross-reactive, but weakly neutralizing (IC 50 > 1 ug ml -1 ) antibody ( 80 ) (Supplemental Figure 5C-E). While the NTD footprint was similar across all antibodies and each interacted with the SD1 domain, available structures showed that only C1596 engaged the RBD within the same protomer (Supplemental Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
“… 23 Despite the hydrophobic cavity domain in the NTD is considered as a promising target for developing neutralizing antibodies against Omicron, it is reported to be susceptible to immune escape, particularly against BA.2. 24 Additionally, no one targeting NTD is licensed for clinical trials yet ( https://clinicaltrials.gov/ ). Nevertheless, it is essential to comprehensively map the epitope landscape of the NTD and explore the conserved neutralization epitopes within it as promising candidates for developing cross-reactive antibodies against continuously evolving variants.…”
Section: Introductionmentioning
confidence: 99%